2013
DOI: 10.1016/j.biomaterials.2013.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Injectable laminin-functionalized hydrogel for nucleus pulposus regeneration

Abstract: Cell delivery to the pathological intervertebral disc (IVD) has significant therapeutic potential for enhancing IVD regeneration. The development of injectable biomaterials that retain delivered cells, promote cell survival, and maintain or promote an NP cell phenotype in vivo remains a significant challenge. Previous studies have demonstrated NP cell – laminin interactions in the nucleus pulposus (NP) region of the IVD that promote cell attachment and biosynthesis. These findings suggest that incorporating la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 59 publications
(61 reference statements)
1
95
1
1
Order By: Relevance
“…This also enables mechanical load transduction, which is important for the synthesis of the NP matrix. 27 Incorporating cells into the CS/HA hydrogel solution reduces clustering and poor distribution of transplanted cells. Moreover, after gelation, the hydrogel provides a temporary three-dimensional matrix to increase cell retention and survival.…”
Section: Discussionmentioning
confidence: 99%
“…This also enables mechanical load transduction, which is important for the synthesis of the NP matrix. 27 Incorporating cells into the CS/HA hydrogel solution reduces clustering and poor distribution of transplanted cells. Moreover, after gelation, the hydrogel provides a temporary three-dimensional matrix to increase cell retention and survival.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,15 However, hydrogel scaffolds lack structural integrity and are probably unsuitable as a tissue-engineering application when not combined with a more rigid structure. The scaffolds used in our present study were fabricated by using a phase-separation technique with a nanofibrous matrix and highly interconnected macropores.…”
Section: Discussionmentioning
confidence: 99%
“…57 NP cells are known to cluster and produce more proteoglycan rich matrix when cultured on soft (<0.5kPa) LM rich substrates as compared to fibronectin or collagen. 57 Francisco et al 58 developed injectable, LM-111 functionalized PEG hydrogels by combining PEG-LM111 conjugates with PEG-octoacrylate and PEG-dithiol under physiological conditions. Bioluminescence studies showed that PEG-LM111 hydrogels significantly improved encapsulated NP cell survival and retention over a 14 day period in IVD explants.…”
Section: Intervertebral Disc Regenerationmentioning
confidence: 99%